Assessment of resources and instructional materials status in the teaching of mathematics in southwestern Nigeria (2010)
Instructional materials are vital to teaching-learning process. It is potent in reducing abstraction that characterizes Mathematics concepts. However, research reports have shown that these materials are grossly unavailable in most schools. Few available ones are either inadequate or underutilized. This paper is a case study of availability, adequacy and utilization of Mathematics instructional materials in southwestern Nigeria. Two (2) schools were randomly selected in each of the 3 senatorial districts of each state, making a total of 36 schools. The findings revealed 34.5%, 18.0% and 22.5% availability, adequacy and utilization rates of instructional materials respectively. The teachers know little implications of the use of instructional materials. Various means of improvisations and sourcing for these instructional materials were recommended. It was also recommended that the teachers should be trained in the appropriate use of instructional materials.